PENGETAHUAN DAN SIKAP MASYARAKAT DALAM MELESTARIKAN LINGKUNGAN HUBUNGANNYA DENGAN PERILAKU MENJAGA KELESTARIAN KAWASAN BUKIT SEPULUH RIBU DI KOTA TASIKMALAYA - Ruli As’ari (GeoEco, 2018)
Tasikmalaya is known as the City of Ten thousand hill. The hill spread to the southeast of the mouth of the depression of Mount Galunggung, with varying heights. The hill is then known as The Ten Thousand Hills of Tasikmalaya or Bukit Ten Thousand Tasikmalaya. The method used in this study is a quantitative correlational description with data collection techniques through observation, questionnaire and documentation study. The results showed; (1) There is a relationship between knowledge about environmental conservation and community behavior in preserving the hill area indicated by the correlation value (r) of 0.355 which is at low level; (2) There is correlation between society attitude in preserving environment and society behavior in preserving hill area indicated by correlation value (r) equal to 0,501 which is at medium level; (3) The relationship between knowledge about environmental conservation and public attitudes in preserving the environment with its behavior in preserving the hill area is indicated by the correlation value (r) of 0.442 which is at a moderate level.Keywords: Knowledge, Attitude, Behavior, hill ten thousand